NILAI PERBANKAN: PERSPEKTIF ASET DAN LIABILITY MANAGEMENT DENGAN KINERJA KEUANGAN - mulyaningtyas, mulyaningtyas (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2025)
This research focuses on the value of banking entities from the perspective of asset liability management, considering financial performance as an intervening variable among banks listed on the IDX between 2022 and 2023. This quantitative study used purposive sampling to select 28 banks that had experienced consecutive profits during the study period. The data were then processed using linear regression and the Sobel test. The results show that asset liability management through financial performance does not affect firm value.